Dynamics in systems of pipes with different movements in its ends (2010)
This document proposes a method of dynamic analysis of pipe systems with different movements at the ends. This methodology takes the response spectrum corresponding to each of the supports, and compared with the simple response method, which uses an envelope in the response spectra of the different supports that is the classic one, in the latter they are not conservative, as It can be seen in the results table of the problem considered. Therefore, the usual practice of considering the spectrum envelope will not be a recommended solution. The use of the consistent or distributed masses is also proposed, and not the discrete or concentrated ones, as is usually done, and also more closely attached to reality.